Znmo4 / tiO2 nanocomposite for sonodynamic antibacterial and preparation method and application thereof
Patent Information
- Application Number
- CN202611007470.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-13
AI Technical Summary
1、本发明提供的一种用于声动力抑菌的ZnMoO4/TiO2纳米复合材料,制备方法简单,其原材料经济易得,并且所得纳米复合材料稳定性高。
Smart Images

Figure CN122894503A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes, its preparation method, and its application. Background Technology
[0002] Bacterial infection at the wound site is a major obstacle to wound healing and can lead to death in severe cases. The mortality rate related to bacterial infections has surpassed that of AIDS and colorectal cancer, becoming the second leading cause of death worldwide. Therefore, antibiotic resistance is receiving increasing attention. The surge in antibiotic overuse in recent years has led to decreased bacterial cell membrane permeability, alterations in drug target proteins, overexpression of efflux pumps, and enhanced drug metabolism. These phenomena have given rise to superbugs and exacerbated bacterial resistance. Therefore, the exploration of innovative antimicrobial materials as wound dressings has become a prominent research area.
[0003] Sonodynamic therapy (SDT) generates reactive oxygen species (ROS) under ultrasound irradiation, directly causing bacterial death without the risk of drug resistance. Furthermore, a major advantage of SDT is its greater penetrability and more concentrated effect on specific infection sites; ultrasound can reach deep organs such as the pancreas and liver.
[0004] TiO2, a widely used acoustic sensitizer, possesses high chemical stability and biocompatibility, effectively transferring ultrasonic energy to cavitation microbubbles and targeting the infection site. Zinc ions are considered to have strong antibacterial properties, and ZnMoO4 exhibits outstanding advantages among all zinc compounds, including low toxicity, broad spectrum, high antibacterial efficiency, strong adhesion, and weather resistance. ZnMoO4 is insoluble and has low toxicity; therefore, it is commonly used as a primary antibacterial and environmentally friendly material in antibacterial coatings. Based on this, this invention explores the acoustic dynamic antibacterial properties of ZnMoO4 / TiO2 nanocomposite materials as acoustic sensitizers. Summary of the Invention
[0005] The purpose of this invention is to provide ZnMoO4 / TiO2 nanocomposite materials as novel acoustic sensitizers for use in the field of acoustic dynamic antibacterial, so that the antibacterial rate of the composite material against Staphylococcus aureus, Escherichia coli and methicillin-resistant Staphylococcus aureus is significantly better than that of the single-component system.
[0006] The technical solution adopted in this invention is: a ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes, wherein the ZnMoO4 / TiO2 nanocomposite material is synthesized by hydrothermal method using zinc chloride, sodium molybdate and titanium dioxide as raw materials.
[0007] Furthermore, by mass ratio, ZnMoO4:TiO2 = 1 : (1 - 2).
[0008] A method for preparing a ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes includes the following steps: (1) Disperse TiO2 powder in deionized water and sonicate it to make it evenly dispersed. Then add Na2MoO4 solution and stir to obtain a suspension. (2) Slowly add ZnCl2 solution to the suspension obtained in step (1), continue stirring, place the resulting mixed solution in a reaction vessel for hydrothermal reaction, and after the reaction is completed, wash with deionized water and ethanol and dry.
[0009] Further, in step (1), TiO2 powder is dispersed in deionized water and sonicated for 1 h - 1.5 h.
[0010] Furthermore, in step (2), the hydrothermal reaction is carried out at 170 ℃ - 190 ℃ for 8 h - 9 h.
[0011] This invention provides the application of a ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes as a acoustic sensitizer in antibacterial applications.
[0012] Further, the method is as follows: ZnMoO4 / TiO2 nanocomposite material is added to the bacterial solution to be treated, and then ultrasonic treatment is performed.
[0013] Furthermore, the ultrasonic conditions are: intensity of 1.0 W / cm². 2 The duty cycle is 50%, the frequency is 1 MHz, and the time is 3 minutes.
[0014] Furthermore, the bacteria include Escherichia coli, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus.
[0015] Furthermore, the concentration of the bacterial solution is 1×10⁻⁶. 6 CFU / mL - 9×10 6 The amount of ZnMoO4 / TiO2 nanocomposite material used was 20 μg / mL to 80 μg / mL.
[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention provides a ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes. The preparation method is simple, the raw materials are economical and readily available, and the obtained nanocomposite material has high stability.
[0017] 2. This invention provides a ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes, which can be used for highly efficient antibacterial activity. The ZnMoO4 / TiO2 nanocomposite material exhibits high antibacterial activity against 10⁻⁶ bacteria under ultrasonic conditions.6 The inhibition rates of CFU / mL of Staphylococcus aureus, Escherichia coli, and methicillin-resistant Staphylococcus aureus reached 96%, 96%, and 95%, respectively, while the dosage of the ZnMoO4 / TiO2 nanocomposite material in the bacterial solution was 20 μg / mL - 80 μg / mL. This indicates that the composite material provided by this invention, as an antibacterial material, requires only a trace amount to achieve ideal antibacterial effects and exhibits excellent antibacterial activity against the three pathogens.
[0018] 3. The ZnMoO4 / TiO2 nanocomposite material provided by this invention for acoustic-dynamic antibacterial purposes significantly improves ROS generation under ultrasonic stimulation and enhances antibacterial efficiency against Escherichia coli, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus, demonstrating significantly superior performance compared to single-component systems. Furthermore, this invention provides a novel approach for the research and development of highly efficient acoustic scavengers for eliminating various bacteria. Attached Figure Description
[0019] Figure 1 Scanning electron microscopy (SEM) spectra of ZnMoO4 (a), TiO2 (b), and ZnMoO4 / TiO2 (c).
[0020] Figure 2 The image shows the EDS spectrum of ZnMoO4 / TiO2.
[0021] Figure 3 The XRD spectra of ZnMoO4 / TiO2 (a), TiO2 (b), and ZnMoO4 (c) are shown.
[0022] Figure 4 The in vitro antibacterial effects of ZnMoO4 (ZM), TiO2 (TO), and ZnMoO4 / TiO2 (ZT) against Escherichia coli, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus are shown in the figure.
[0023] Figure 5 This image shows the ability of ZnMoO4 (ZM), TiO2 (TO), and ZnMoO4 / TiO2 (ZT) materials to generate extracellular ROS concentration after sonication using a fluorescence spectrophotometer via a DCFH-DA probe.
[0024] Figure 6 This image shows the ability of ZnMoO4 (ZM), TiO2 (TO), and ZnMoO4 / TiO2 (ZT) materials to generate intracellular ROS concentration after sonication using a DCFH-DA probe via a fluorescence spectrophotometer.
[0025] Figure 7The cell viability of mouse fibroblasts (L929) was obtained by MTT assay using ZnMoO4 / TiO2 nanocomposite materials at different concentration gradients (5 μg / mL, 10 μg / mL, 20 μg / mL, 40 μg / mL, 80 μg / mL, 160 μg / mL). Detailed Implementation
[0026] The present invention will be further described below with reference to specific embodiments.
[0027] Example 1: ZnMoO4 / TiO2 nanocomposite material
[0028] (I) Preparation of ZnMoO4 / TiO2 nanocomposites
[0029] (1) Dissolve 429.2 mg of sodium molybdate dihydrate (Na2MoO4·2H2O) in 10 mL of deionized water and stir for 10 min at room temperature to completely dissolve it, thus obtaining a Na2MoO4 solution.
[0030] (2) Dissolve 254.8 mg of zinc chloride (ZnCl2) in 10 mL of deionized water and stir for 10 min at room temperature to completely dissolve it, thus obtaining a ZnCl2 solution.
[0031] (3) Disperse 600 mg TiO2 powder in 20 mL of deionized water and sonicate for 1 h to make it evenly dispersed. Then add Na2MoO4 solution and stir to obtain a suspension.
[0032] (4) The ZnCl2 solution was slowly added dropwise to the suspension of Na2MoO4 and TiO2 obtained in step (3), and the mixture was stirred for another 30 min at room temperature. The resulting mixed solution was then poured into a reaction vessel and hydrothermally reacted at 180 °C for 8 h. After the reaction was completed, the mixture was washed several times with deionized water and ethanol alternately, and then placed in an oven and dried at 60 °C for 12 h to obtain the ZnMoO4 / TiO2 nanocomposite material.
[0033] (II) Result Characterization
[0034] 1. SEM Analysis
[0035] The microstructure of the material was observed using scanning electron microscopy (SEM). Figure 1 It can be observed that the ZnMoO4(a) surface is relatively smooth and the structure is regular. The TiO2(b) particles are spherical. The ZnMoO4 / TiO2(c) composite material retains the macroscopic structural framework of ZnMoO4, while the surface is covered with a large number of TiO2 nanoparticles, which proves that the ZnMoO4 / TiO2 nanocomposite material was successfully prepared.
[0036] 2. EDS Analysis
[0037] Elemental analysis of ZnMoO4 / TiO2 composites was performed using EDS, from Figure 2 It can be observed that a composite material containing four elements—Ti, Zn, Mo, and O—was successfully synthesized. The Ti and O elements are derived from TiO2, while the Zn, Mo, and O elements are derived from ZnMoO4, proving the successful preparation of the ZnMoO4 / TiO2 composite material. Figure 2 It can be observed that the characteristic peaks of each element match, Ti, Mo and Zn coexist, and the content of each element in the complex is in proportion.
[0038] 3. XRD Analysis
[0039] X-ray diffraction patterns and crystal structures of ZnMoO4, TiO2, and ZnMoO4 / TiO2 were determined using XRD. Figure 3 It can be observed that, by comparing the experimental diagram and the standard card diagram, TiO2 ( Figure 3 (b) The positions of the diffraction peaks in ZnMoO4 basically match those on the standard card. Figure 3 (c) exhibits extremely high crystallinity and good phase purity, with diffraction peak positions perfectly matching the standard card. ZnMoO4 / TiO2 composite material ( Figure 3 The spectrum in (a) shows that ZnMoO4 and TiO2 maintained their respective crystal structures during the composite process, proving the successful preparation of the ZnMoO4 / TiO2 composite material.
[0040] Example 2: Application of ZnMoO4 / TiO2 nanocomposite materials in antibacterial applications
[0041] I. In vitro antibacterial experiment of ZnMoO4 / TiO2 nanocomposite materials
[0042] Methods: The antibacterial effects of ZnMoO4 / TiO2 nanocomposite materials against *Escherichia coli*, *Staphylococcus aureus*, and methicillin-resistant *Staphylococcus aureus* were assessed using a bacterial colony counting method. First, each of these three bacteria was inoculated into LB broth medium and incubated overnight at 37 °C with shaking at 180 rpm. The overnight culture was then diluted to 10⁻¹⁰. 6 The concentration of the mother liquor for preparing the ZnMoO4 / TiO2 nanocomposite material was 1 mg / mL, and the concentration of the mother liquor was 1 mg / mL. The ultrasonic (US) conditions were 1.0 W / cm². 2 The interaction schemes of ZnMoO4 / TiO2 nanocomposites with three different bacteria at 3 min, 1 MHz, and 50% duty cycle are shown in Tables 1-3. Subsequent dilution and plating were performed; the results are shown in [Table 1-3]. Figure 4 .
[0043] Table 1. Co-treatment regimens of different groups with Escherichia coli
[0044] The final concentration of the ZnMoO4 / TiO2 nanocomposite was 60 μg / mL.
[0045] Table 2. Co-treatment regimens of different groups with Staphylococcus aureus
[0046] The final concentration of the ZnMoO4 / TiO2 nanocomposite was 20 μg / mL.
[0047] Table 3. Co-treatment regimens of different groups with methicillin-resistant Staphylococcus aureus
[0048] The final concentration of the ZnMoO4 / TiO2 nanocomposite was 80 μg / mL.
[0049] Depend on Figure 4 It can be seen that the ZnMoO4 / TiO2 nanocomposite material exhibits good performance under ultrasonic conditions for 10... 6 The inhibition rates of CFU / mL Staphylococcus aureus, Escherichia coli, and methicillin-resistant Staphylococcus aureus reached 96%, 96%, and 95%, respectively.
[0050] Example 3: Detection of the acoustic-dynamic performance level of ZnMoO4 / TiO2 nanocomposite material in response to ultrasound.
[0051] (I) Comparison of extracellular ROS generation levels in ZnMoO4 / TiO2 nanocomposites
[0052] Methods: A commercially available ROS detection kit (2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA)) was selected to evaluate the performance of each different sample in US (1.0 W / cm²). 2 The level of reactive oxygen species (ROS) generated under stimulation (50% duty cycle, 1 MHz, 3 min) was determined. Specifically, 10 μL of (DCFH-DA) solution (10 mM) was dispersed in 45 μL of ethanol, then mixed with 200 μL of NaOH solution (0.1 M) in the dark at room temperature for 30 min, followed by dilution with 1 mL of PBS. Samples from different control groups were mixed with the above solution and stimulated with US for 3 min as described above. Generally, stronger fluorescence intensity indicates a greater amount of ROS generated. The fluorescence intensity of 2′,7′-dichlorofluorescein (DCF) was measured at 525 nm using a fluorescence spectrophotometer with an excitation wavelength of 485 nm.
[0053] Table 4 Summary of Extracellular Fluorescence Intensities (Emission Wavelength 525 nm) of ZnMoO4 / TiO2 and its Monomers
[0054] From Table 4 and Figure 5 It can be observed that after 3 min of US stimulation, the ZnMoO4 / TiO2 composite material showed a more significant and stronger fluorescence at 525 nm, which proves that the total amount of ROS generated by the ZnMoO4 / TiO2 composite material under ultrasonic stimulation is more significant than that of ZnMoO4 and TiO2.
[0055] (II) Comparison of intracellular ROS generation levels in ZnMoO4 / TiO2 nanocomposites
[0056] Methods: A commercially available ROS detection kit (2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA)) was selected to evaluate the performance of each different sample in US (1.0 W / cm²). 2 The levels of reactive oxygen species (ROS) produced intracellularly by three bacteria—Staphylococcus aureus, Escherichia coli, and methicillin-resistant Staphylococcus aureus—were measured under stimulation at 50% duty cycle, 1 MHz, and 3 min. The specific procedure involved first preparing 2 mL of bacterial suspension (bacterial concentration of 5 × 10⁻⁶). 9 Centrifuge at 6000 rpm for 5 min (CFU / mL), discard the supernatant, add 2 mL of DCFH-DA solution (10 μM), and incubate at 37 ℃ in a shaking incubator for 1 h. After incubation, centrifuge at 6000 rpm for 5 min, wash twice with PBS, and add 2 mL of PBS to disperse. At this point, the bacterial concentration is still 5 × 10⁻⁶. 9 CFU / mL. Next, the bacteria and material were co-treated under the aforementioned US conditions. Then, as described in the previous steps, the fluorescence intensity of 2′,7′-dichlorofluorescein (DCF) was measured at 525 nm using a fluorescence spectrophotometer with an excitation wavelength of 485 nm.
[0057] Table 5 Summary of intracellular fluorescence intensity of Escherichia coli (emission wavelength 525 nm)
[0058] Table 6 Summary of Intracellular Fluorescence Intensities of Staphylococcus aureus (Emission Wavelength 525 nm)
[0059] Table 7 Summary of Intracellular Fluorescence Intensities (Emission Wavelength 525 nm) of Methicillin-Resistant Staphylococcus aureus
[0060] From Table 5-7 and Figure 6 It can be observed that after 3 minutes of ultrasonic stimulation, the ZnMoO4 / TiO2 composite material showed significantly stronger fluorescence at 525 nm for Staphylococcus aureus, Escherichia coli, and methicillin-resistant Staphylococcus aureus. This proves that the ZnMoO4 / TiO2 composite material generates a more significant amount of ROS under ultrasonic stimulation compared to ZnMoO4 and TiO2.
[0061] Example 4 Cytotoxicity assessment of ZnMoO4 / TiO2 nanocomposites
[0062] Methods: Mouse fibroblasts (L929) were used as a model to evaluate the biocompatibility of ZnMoO4 / TiO2 nanocomposites using an MTT assay. The cells were cultured in RPMI-1640 medium supplemented with 10% fetal bovine serum (FBS) at 37 °C and 5% CO2 for 24 h, followed by culturing in 96-well plates at a density of approximately 8000 cells per well for another 24 h. Then, different concentrations (5 μg / mL, 10 μg / mL, 20 μg / mL, 40 μg / mL, 80 μg / mL, 160 μg / mL) of ZnMoO4 / TiO2 nanocomposites were co-cultured with the cells (approximately 8000 cells per well) for 24 h. MTT solution was then added, and after 4 h of incubation, the liquid in the 96-well plates was removed, and 150 μL of DMSO solution was added to each well. The absorbance at 490 nm was measured using a microplate reader, and cell viability was calculated.
[0063] pass Figure 7 It can be seen that for mouse fibroblasts (L929), the survival rate of cells with a ZnMoO4 / TiO2 nanocomposite concentration of less than 160 μg / mL is above 80%. Therefore, it can be concluded that the ZnMoO4 / TiO2 nanocomposite has no cytotoxicity and good biocompatibility within the antibacterial concentration range.
Claims
1. A ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes, characterized in that, The ZnMoO4 / TiO2 nanocomposite material was synthesized by a hydrothermal method using zinc chloride, sodium molybdate, and titanium dioxide as raw materials.
2. The ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes according to claim 1, characterized in that, By mass ratio, ZnMoO4:TiO2 = 1 : (1 - 2).
3. A method for preparing a ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes as described in claim 1 or 2, characterized in that, Includes the following steps: (1) Disperse TiO2 powder in deionized water and sonicate it to make it evenly dispersed. Then add Na2MoO4 solution and stir to obtain a suspension. (2) Slowly add ZnCl2 solution to the suspension obtained in step (1), continue stirring, place the resulting mixed solution in a reaction vessel for hydrothermal reaction, and after the reaction is completed, wash with deionized water and ethanol and dry.
4. The preparation method according to claim 3, characterized in that, In step (1), TiO2 powder is dispersed in deionized water and sonicated for 1 h - 1.5 h.
5. The preparation method according to claim 3, characterized in that, In step (2), the hydrothermal reaction is carried out at 170 ℃ - 190 ℃ for 8 h - 9 h.
6. The application of the ZnMoO4 / TiO2 nanocomposite material for acoustic-dynamic antibacterial purposes as described in claim 1 or 2 as an acoustic sensitizer in antibacterial applications.
7. The application according to claim 6, characterized in that, The method is as follows: Add ZnMoO4 / TiO2 nanocomposite material to the bacterial solution to be treated, and then treat with ultrasound.
8. The application according to claim 7, characterized in that, The ultrasonic conditions were: intensity 1.0 W / cm². 2 The duty cycle is 50%, the frequency is 1 MHz, and the time is 3 minutes.
9. The application according to claim 7, characterized in that, The bacteria include Escherichia coli, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus.
10. The application according to claim 7, characterized in that, The concentration of the bacterial solution is 1×10⁻⁶. 6 CFU / mL - 9×10 6 The amount of ZnMoO4 / TiO2 nanocomposite material used was 20 μg / mL to 80 μg / mL.